A Roundup herbicide causes high mortality and impairs development of Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) - Defarge, N.; Otto, M.; Hilbeck, A. (The Science of the total environment, 2023)
Glyphosate has and is being used extensively in herbicide formulations worldwide. Thus, glyphosate-based herbicides (GBH) substantially add to the environmental load of pesticides and warrant a strict risk assessment. Ecotoxicological testing of herbicides focuses on non-target plants and higher animals while direct effects on arthropods are only cursory tested on the premise of contact exposure. However, oral exposure, as we show in our case, can be highly relevant for systemic pesticides, such as GBH. Specifically, in crop systems including genetically modified crops that are tolerant to GBH, these herbicides and their breakdown products are present both internally and externally of the crop plants and, therefore, are ingested by the crop-associated arthropod fauna. We tested the effects of oral uptake of the Roundup formulation WeatherMax on larvae of the lacewing Chrysoperla carnea, a model organism in ecotoxicity testing programs. Long-term oral exposure of C. carnea larvae throughout its juvenile life stages was tested with concentrations ranging from 0.001 to 1 % dilution, thus, lower than the 1.67 % recommended for field applications. Inhibition of metamorphosis was observable at 0.1 % but at a concentration of 0.5 %, GBH significantly impaired cocoon formation and led to massive lethal malformations. At GBH concentration of 1 % half of the individuals remained permanent larvae and no adult hatched alive. The effects observed followed a clear dose-response relationship. The hazard caused by direct insecticidal action of GHB after oral uptake is highly relevant for the environmental safety and reveals a gap in regulatory risk assessments that should urgently be addressed, specifically in light of the on-going insect decline. [Display omitted] •Herbicides are only cursory tested for effects on non-target arthropods and usually do not include oral exposure•C. carnea larvae were exposed to a Glyphosate herbicide via food at concentrations below the recommended application rate•Oral exposure resulted in developmental arrest, impaired cocoon formation and high mortality•The identified hazard is highly relevant for risk assessment and warrants a fresh look at current pesticide testing schemes